2016
DOI: 10.1177/0263617415623421
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption-based approach to determine the size and mass of humic acids molecules

Abstract: The state of sodium humate in aqueous solution and on a solid surface is studied using various methods. It is shown that in aqueous solution at neutral pH and low ionic strength this substance exists in an associated state. The values of molecular mass of the molecules in the preparation studied (Aldrich) are determined to be 1, 3-6 and 15 kDa. A new adsorption-based approach for initial estimation of the molecular mass and size of humic acid molecules is proposed, which can be used instead of any specific sop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
0
11
1
Order By: Relevance
“…A similar approach used by Esfahani et al ( 2015 ) detected three populations in SRHA, SRFA and Aldrich humic acids (10–100, 100–1,000 nm, and >1 μm) on the basis of volume based distributions. Volume distributions were also preferred by Tarasevich et al ( 2016 ) who analyzed the sodium salt of Aldrich humic acids and divided it into three fractions called nanoparticles (30–150 nm), submicroparticles (200–700 nm), and microparticles (1.6–5.6 μm).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar approach used by Esfahani et al ( 2015 ) detected three populations in SRHA, SRFA and Aldrich humic acids (10–100, 100–1,000 nm, and >1 μm) on the basis of volume based distributions. Volume distributions were also preferred by Tarasevich et al ( 2016 ) who analyzed the sodium salt of Aldrich humic acids and divided it into three fractions called nanoparticles (30–150 nm), submicroparticles (200–700 nm), and microparticles (1.6–5.6 μm).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration, pH, ionic strength, and nature of the counter-ion influence the size and shape of the dissolved organic species (Durce et al, 2016 ). However, many fundamental questions relating, in particular, to the physicochemical characteristics of humic and fulvic molecules are yet to be answered (Klučáková, 2016 ; Tarasevich et al, 2016 ). The data on the molecular mass and size of humic molecules reported in literature are rather confusing and are strongly influenced by differences in experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of titration experiments with acidic functional groups showed that the carboxyl group content in FA was approximately three times the phenolic hydroxyl group content. Combined with the spectral data for oxygen-containing functional groups in the range of 1000-1800 cm À1 and the relative content of oxygen, the molecular 3,21,[23][24][25][26][27][29][30][31] with the ndings of past research on HA and FA, the numbers and positions of functional groups were continuously adjusted to approximate the experimental test parameters. The resulting two-dimensional planar molecular structure model of FA is shown in Fig.…”
Section: Establishment Of the Molecular Structure Model And Its Theormentioning
confidence: 99%
“…Research carried out in various countries suggests that the efficacy of humic acid depends on its extremely complex chemical structure, which makes biochemical investigations elaborate, costly, and difficult to reproduce [ 7 ]. Many fundamental questions relating, in particular, to the physicochemical characteristics of humic and fulvic molecules are yet to be answered [ 21 , 22 ]. Differences in the obtained values have been attributed to either the variability of humic substances or the intrinsic limitations of methods when applied to poly-disperse humic systems [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%